2006
DOI: 10.1159/000089614
|View full text |Cite
|
Sign up to set email alerts
|

Postthyroplasty Implant Extrusion

Abstract: The case of a 57-year-old gentleman with a left-sided vocal cord palsy following a surgical procedure done elsewhere is being reported. His main problem was dysphonia, and speech therapy did not improve his voice much. A thyroplasty type 1 was done to improve his voice. A Silastic implant was inserted for medialization of vocal cords with a good postoperative result. The patient was followed up in the clinic and presented again 7 months after surgery with extrusion of the Silastic implant. Quite remarkably, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It has been suggested that extrusion is more likely to occur in females than males because females generally have a smaller larynx. 7,8 The reported incidence of thyroplasty extrusion has ranged from 0.8 to 9.8%, and it has been seen with the use of various nonresorbable implants. 6 In a review by Giovanni et al, 1 of 13 patients who underwent Gore-Tex vocal fold medialization experienced an extrusion.…”
mentioning
confidence: 99%
“…It has been suggested that extrusion is more likely to occur in females than males because females generally have a smaller larynx. 7,8 The reported incidence of thyroplasty extrusion has ranged from 0.8 to 9.8%, and it has been seen with the use of various nonresorbable implants. 6 In a review by Giovanni et al, 1 of 13 patients who underwent Gore-Tex vocal fold medialization experienced an extrusion.…”
mentioning
confidence: 99%